A Low Protein Diet Alters Bone Material Level Properties and the Response to In Vitro Repeated Mechanical Loading. (14th August 2014) - Dubois-Ferrière, Victor; Rizzoli, René; Ammann, Patrick
Abstract : Low protein intake is associated with an alteration of bone microstructure and material level properties. However, it remains unknown whether these alterations of bone tissue could influence the response to repeated mechanical loading. The authors investigated the in vitro effect of repeated loading on bone strength in humeri collected from 20 6-month-old female rats pair-fed with a control (15% casein) or an isocaloric low protein (2.5% casein) diet for 10 weeks. Bone specimens were cyclically loaded in three-point bending under load control for 2000 cycles. Humeri were then monotonically loaded to failure. The load-displacement curve of the in vitro cyclically loaded humerus was compared to the contralateral noncyclically loaded humerus and the influence of both protein diets. Material level properties were also evaluated through a nanoindentation test. Cyclic loading decreased postyield load and plastic deflection in rats fed a low protein diet, but not in those on a regular diet. Bone material level properties were altered in rats fed a low protein diet. This suggests that bone biomechanical alterations consequent to cyclic loading are more likely to occur in rats fed a low protein diet than in control animals subjected to the same in vitro cyclic loading regimen.